Atopic dermatitis: pathomechanisms and lessons learned from novel systemic therapeutic options. (18th August 2022) - Bieber, T.; Paller, A.S.; Kabashima, K.; Feely, M.; Rueda, M.J.; Ross Terres, J.A.; Wollenberg, A.
Abstract: Atopic dermatitis (AD) is a chronic, heterogenous, inflammatory skin disorder associated with a high skin‐related health burden, typically starting in childhood and often persisting into adulthood. AD is characterized by a wide range of clinical phenotypes, reflecting multiple underlying pathophysiological mechanisms and interactions between genetics, immune system dysregulation and environmental factors. In this review, we describe the diverse cellular and molecular mechanisms involved in AD, including the critical role of T‐cell‐driven inflammation, primarily via T helper (Th) 2‐ and Th17‐derived cytokines, many of which are mediated by the Janus kinase (JAK) signaling pathway. These local inflammatory processes interact with sensory neuronal pathways, contributing to the clinical manifestations of AD, including itch, pain and sleep disturbance. The recent elucidation of the molecular pathways involved in AD has allowed treatment strategies to evolve from broad‐acting systemic immunosuppressive therapies to more targeted agents, including JAK inhibitors and cytokine‐specific biologic agents. Evidence from the clinical development of these targeted therapies has reinforced and expanded our understanding of the pathophysiological mechanisms underlying AD and holds promise for individualized treatment strategies tailored to specific AD subtypes.